Detection of Neisseria meningitidis, Streptococcus pneumoniae and Haemophilus influenzae in Cerebrospinal Fluid by Multiplex PCR for Diagnosis of Acute Bacterial Meningitis in Paediatric Population (Bangladesh Journal of Medical Microbiology, 2017)
The present study was done to evaluate a multiplex PCR based method for simultaneous detection of Neisseria meningitidis, Streptococcus pneumoniae and Haemophilus influenzae in CSF. A cross sectional study was carried out with 140 children (2 months to 12 years of age) with clinical suspicion of acute meningitis during July 2010 to June 2011. Three species-specific primers were used along with universal primers of bacterial gene 16S rRNA, in a two-stage PCR assay for diagnosis of acute bacterial meningitis.Among 140 patients, 42 (30%) cases were diagnosed as bacterial meningitis and other 98 (70%) as viral meningitis by clinical and cytobiochemical criteria. Out of 42 bacterial meningitis cases, 9 (21.43%) were positive by Gram stain.These 9 cases were also positive by bacterial culture and PCR. Again, 15 (35.71%) were positive by bacterial culture which were also PCR positive. In 27 cases (out of 42), the etiologic diagnosis was not possible using routine bacteriological methods; in 11 of these patients, the etiologic agents were identified by PCR. In addition, PCR recognized 5 more cases whose etiologic diagnosis was not possible, as they were identified by universal primer of 16S rRNA. Hence, among 31 (73.81%) PCR positive cases, 12 (38.71%) were S. pneumoniae, 10 (32.26%) were H. influenzae, 4 (12.9%) were N. meningitidis and 5 (16.13%) were other bacteria.Among the antibiotic users, bacterial meningitis case detection by PCR was higher (65.52%) than that of culture (10.34%) and Gram staining (6.90%). The overall sensitivity and specificity of PCR assay was 100% and 66% respectively when bacterial culture was considered as gold standard. PCR can be used as a valuable supplementary diagnostic technique in routine clinical practice for diagnosis of acute bacterial meningitis in hospital setting.Bangladesh J Med Microbiol 2017; 11 (2): 9-16